Resisting epistemic violence in global mental health: Listening to local understandings of mental health and emotional distress among victims and ex-guerrilla members in Southern Colombia - María Cecilia Dedios Sanguineti; Laura Fonseca; Rochelle A. Burgess; Natalia Concha; Mónica González; Norha Vera San Juan; Mónica Carreño; Kely Johana Palacio; María Fernanda Sotto; Sandra Jovchelovitch (SSM - Mental Health)
Background: While there is consensus that local knowledge is important to build better mental health responses, integration of this knowledge into mental health services remains a work in progress. In this paper, we explore local understandings of mental health, mental illness, well-being and emotional distress building dialogical spaces that enable community perspectives to inform academic knowledge and health systems. Methods: We identified local understandings of mental health, emotional distress, and wellbeing among two conflict-affected communities in Southern Colombia, including victims of the conflict and FARC ex-combatants. We conducted focus groups in Florencia (n = 8) and La Montañita (n = 7) (N = 99). Data was analysed using thematic analysis. Results: We found a lay theory of mind emphasising the mind-body-context relationship as central for health and wellbeing. Mental health and mental illness are explained through biomedical categories underpinned by social representations of ‘madness’ and the stigma associated with the conflict and using services in Colombia. Wellbeing and emotional distress are determined by relational, political and economic factors, and understood in relation to culture, sociability, religiosity, nature and physical health. Discussion: Accounting for local knowledge allows working with community members to identify how their experiences, values, beliefs, and the context they live in can support or hinder their emotional wellbeing. Central to this effort is to open hegemonic biomedical models to transformational dialogues that integrate the perspective and needs of the communities we work with. Our study provides actionable insights relevant for community-based mental health and primary care services, as well as those services across sectors that can contribute to the mental health of this population.